2011
DOI: 10.1038/aps.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and management of Toxoplasma gondii infection in pregnancy and infancy: a prospective study

Abstract: Aim: Toxoplasma gondii infection during pregnancy poses a serious risk to the fetus, therefore timely and accurate diagnosis is essential. The aim of this study was to estimate the frequency of congenital infection via evaluating mother's immunological status and the possibility to improving the diagnostic and therapeutic approaches. Methods: Eighty five mothers with Toxoplasma seroconversion and their offspring were enrolled (among them, 2 spontaneous abortions were documented in the first trimester). Prenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Table 1 provides an overview of all studies included in the final sample and of all data elements used during the data analysis process. The 41 studies were distributed into the previously determined three categories as follows: DIAGNOSTIC METHODS [2,4,5,8,9,12,14,16,17,20,25,27,29,32,34,35,37,41,42 (nineteen studies)]; DIAGNOSIS IN PREGNANT WOMEN [ 3,7,10,14,25,27,35,42,46,50,51,53, 59 thirteen studies)]; DIAGNOSIS IN NEONATES [7,8,11,20,61,64,65,67,68,70,71,72 (twelve studies)] and DIAGNOSIS IN INFANTS [1,3,5,9,11,12,20,27,…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides an overview of all studies included in the final sample and of all data elements used during the data analysis process. The 41 studies were distributed into the previously determined three categories as follows: DIAGNOSTIC METHODS [2,4,5,8,9,12,14,16,17,20,25,27,29,32,34,35,37,41,42 (nineteen studies)]; DIAGNOSIS IN PREGNANT WOMEN [ 3,7,10,14,25,27,35,42,46,50,51,53, 59 thirteen studies)]; DIAGNOSIS IN NEONATES [7,8,11,20,61,64,65,67,68,70,71,72 (twelve studies)] and DIAGNOSIS IN INFANTS [1,3,5,9,11,12,20,27,…”
Section: Resultsmentioning
confidence: 99%
“…These two questions still remain very controversial. Surprisingly, only few reports on cerebral US findings in case of fetal infection have been reported [3,[7][8][9][10][11] . Whatever the recommendation on systematic maternal serum screening across different countries, we consider that the cerebral signs associated with congenital toxoplasmosis should be more largely diffused.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the recommendation on systematic maternal serum screening across different countries, we consider that the cerebral signs associated with congenital toxoplasmosis should be more largely diffused. Except for cases of significant ventricular dilation, very few studies have focused on fetal cerebral signs in congenital toxoplasmosis [3,[7][8][9][10][11]] . Yet, a better knowledge of these signs would be of interest as fetal prognosis largely depends on the severity of the cerebral damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study in Italy, prenatal polymerase chain reaction showed that seven of 50 (14%) had positive immunological status for toxoplasmosis, and 17% of their infants were infected at 1 year serological follow-up [18]. In a study in Shanghai, China to explore the prevention and treatment of early pregnancy TORCH infection (toxoplasmosis, other infections, rubella, cytomegalovirus, herpes simplex 2), 3.28% of cases were positive for Toxoplasma IgM antibody [19].…”
Section: S73mentioning
confidence: 99%